Pengaruh Kompensasi Finansial terhadap Kinerja Karyawan pada Koperasi Kredit Swasti Sari Kota Kupang - Soleman Nub Uf; Marsi Bani (EKALAYA : Jurnal Ekonomi Akuntansi, 2026)
Financial compensation is one of the key factors influencing employee motivation and performance. However, delays or inconsistencies in providing incentives and allowances may reduce employees' work motivation and productivity. This study aims to analyze the effect of financial compensation on employee performance at the Swasti Sari Credit Union in Kupang City. A quantitative approach with a survey method was employed. The study population consisted of 32 employees, all of whom were selected as respondents using a saturated sampling technique. Data were collected through questionnaires, observations, interviews, and documentation, and were analyzed using descriptive statistics and simple linear regression. The findings revealed that financial compensation was categorized as very good, with an achievement score of 80.83%, while employee performance was also categorized as very good, with an achievement score of 81.46%. The regression analysis produced the equation Y = 13.331 + 0.274X, with a t-value of 2.459 and a significance level of 0.020 (<0.05), indicating that financial compensation has a positive and significant effect on employee performance. It can be concluded that improving financial compensation contributes to better employee performance. Therefore, management is encouraged to maintain the existing compensation system while enhancing the consistency, transparency, and timeliness of incentive distribution to optimize employee performance.